THE IMPACT OF DEPRESSION ON MATERNAL RESPONSES TO INFANT FACES IN PREGNANCY. Issue 6 (9th November 2015) - Macrae, J.A.; Pearson, R.M.; Lee, R.; Chauhan, D.; Bennert, K.; Burns, A.; Baxter, H.; Evans, J.
ABSTRACT: Research has suggested that prenatal depression may be associated with disrupted maternal responses to infant stimuli, with depressed pregnant women not showing the bias toward distressed infants as that observed in nondepressed pregnant women. The current study examined the effects of depression on self‐ reported responses to infant stimuli, in early pregnancy. Women with clinical depression ( n = 38), and nondepressed women ( n = 67) were recruited from a wider cognitive behavioral therapy trial. They completed Maternal Response Scales in which they were presented with images of distressed, neutral, and happy infant faces, with no time limit. The women rated their responses to these images along three dimensions—wanting to comfort, wanting to turn away, and feelings of anxiety—using Likert scales via a computerized task. There was evidence that women with depression in pregnancy showed different responses than did women without depression. Women with depression were substantially more likely to be in the highest quartile for ratings of wanting to turn away, odds (OR) ratio = 4.15, 95% confidence intervals (CIs) = 1.63–10.5, p = .003, and also were substantially less likely to be in the highest quartile for wanting to comfort a distressed infant face, OR = 0.22, 95% CIs = 0.09–0.54, p < .001. Findings are consistent with there being both a heightened avoidant and a reduced comforting response toward distressed infants in depressed pregnant women, providing some support that depression disrupts maternal preparations at a conscious level.